Relationship of Sleep Quality with Menstrual Cycle in Teenagers - Fatmaningsih, Nurul Khotimah; Koeryaman, Mira Trisyani; Rosidin, Udin (GLOBAL HEALTH SCIENCE GROUP, 2024)
Adolescence is a very important time in the process of reproductive maturity, and adolescence has a high risk of being associated with sleep disorders. It is important for teenagers, especially schoolchildren, to have a good quality of sleep in order to be able to perform academic activities. However, students are very vulnerable to poor sleep quality, which will affect both psychological and physiological imbalances, including menstrual cycles. The aim of this study is to find out the relationship between sleep quality and the menstrual cycle in adolescents in SMAN 1 Sumedang. This research method uses a correlational analytical design with a cross-sectional approach. A large sample of 438 pupils was obtained. The research instrument used the PSQI questionnaire to measure sleep quality, consisting of categories such as objective sleep quality, sleep latency, sleep duration, sleep efficiency, daytime dysfunction, sleep disorders, sleeping pills, and menstrual cycle questionnaires over the last 3 months. The results of this study were obtained from 244 people who had good sleep quality. 48.4% had normal menstrual cycle patterns, and 7.3% had abnormal ones. And for 194 people with poor sleep quality, 25.6% had normal periods and 18.7% had unnormal periods. In the statistics, the chi-square test obtained a p-value of 0.000, so it can be concluded that there is a meaningful relationship between sleep quality and menstrual cycle in adolescents in SMAN 1 Sumedang.